Effects of inorganic and organic nutrients combindly used on yield and quality of groundnut (Arachis hypogaea L.) - Seran, Thayamini H (Bangladesh Journal of Scientific and Industrial Research, 2018)
This experiment was done to study the effects of combined use of inorganic and organic nutrients on yield and quality of groundnut (Arachis hypogaea L.). Treatment were full doses of NPK fertilizers (N:P2O5:K2O @ 16:45:45 kg/ha) alone, Farmyard manure (FYM) @ 15 ton/ha alone and half doses of NPK fertilizers with FYM @ 7.5 ton/ha as basal application with or without N @14 kg/ha as top dressing. The results show that highest seed yield (2558.02 kg/ha) was obtained in NPK @ 22.0:22.5:22.5 kg/ha plus FYM @ 7.5 ton/ha followed by FYM @15 ton/ha with N @ 14 kg/ha (2521.98 kg/ha). The highest protein (29.9 g) and oil (45.6%) contents were recorded in plot treated with FYM alone. It can be concluded that when compared to the standard control, NPK fertilizers @ 22.0:22.5:22.5 kg/ha with FYM @ 7.5 ton/ha gave higher seed yield as well as protein (28.8 g) and oil (38%) contents with less environmental impact. Bangladesh J. Sci. Ind. Res.53(4), 289-296, 2018